A new tool for the quantitative analysis of dendritic filopodial motility. (24th September 2014) - Tárnok, Krisztián; Gulyás, Márton; Bencsik, Norbert; Ferenc, Katalin; Pfizenmaier, Klaus; Hausser, Angelika; Schlett, Katalin
Abstract Dendritic filopodia are tiny and highly motile protrusions formed along the dendrites of neurons. During the search for future presynaptic partners, their shape and size change dynamically, with a direct impact on the formation, stabilization and maintenance of synaptic connections both in vivo and in vitro. In order to reveal molecular players regulating synapse formation, quantitative analysis of dendritic filopodia motility is needed. Defining the length or the tips of these protrusions manually, however, is time consuming, limiting the extent of studies as well as their statistical power. Additionally, area detection based on defining a single intensity threshold can lead to significant errors throughout the image series, as these small structures often have low contrast in fluorescent images. To overcome these problems, the open access Dendritic Filopodia Motility Analyzer, a semi‐automated ImageJ/Fiji plugin was created. Our method calculates the displacement of the centre of mass (CoM) within a selected region based on the weighted intensity values of structure forming pixels, selected by upper and lower intensity thresholds. Using synthetic and real biological samples, we prove that the displacement of the weighted CoM reliably characterizes the motility of dendritic protrusions. Additionally, guidelines to define optimal parameters of live cell recordings from dendritic protrusions are provided. © 2014 International Society for Advancement of Cytometry